Influence of Intellectual Capital on Operational Performance through Innovation Capability in Indonesia’s Defence Industry - Pratiwi Dwi Citrasari; Kusuma Ratnawati; Djumilah Hadiwidjojo (Media Ekonomi dan Manajemen, 2022)
This research examines the impact of intellectual capital on operational performance through innovation capabilities in the defence industry in Indonesia, PT. Pindad (Persero). Network processes within the company are assessed by internal performance, which is described by the company's operational performance. 142 employees who work in the production function were sampled in this research using the probability-sampling method with a stratified random sampling type. SEM-PLS was used as a data analysis model. Human capital, structural capital and social capital are three components used in the research. This study provides empirical evidence that these three components influence operational performance. In addition, it is known that human capital, structural capital, and social capital affect innovation capability, and the company's operational performance is influenced by innovation capability. In an indirect relationship, the results interpret that the influence of human capital, structural capital and social capital on the company's operational performance can be through innovation capability. This research provides input to the defence industry to improve performance by increasing the intellectual capital owned by the company without ignoring the importance of innovation capability.